Stakeholder Perceptions of the Provision of Reproductive Health Services by School-Based Health Centers as They May Inform Public Policy. (February 2015) - Herrman, Judith W.
The provision of reproductive health services (RHS) by school-based health centers (SBHCs) is the subject of much controversy. Ideological differences about the role of schools in health care and the sexual activity of youth frame this debate. The purpose of this study was to determine the perspectives of key stakeholders related to access to RHS in SBHCs. Individual, semistructured interviews were conducted with 50 adult stakeholders. Template analysis yielded rich answers to the interview questions. Nine overarching themes emerged during thematic analysis. Subthemes and exemplar quotes revealed important insights into public opinion about RHS at SBHCs. Findings reflect strong stakeholder support for the inclusion of RHS in SBHCs as a way to promote teen sexual health. Nurses have an important role in influencing policies related to teen reproductive health such as those addressed in this study.